Title: Let’s Talk LMCC (S01E02): Diabetes Mellitus - Susan Wang; Meryem Talbo; Alice Y.Y. Cheng; Katherine Lan; Esther ShinHyun Kang (McGill Journal of Medicine, 2023)
Welcome to the McGill Journal of Medicine (MJM) LMCC review. This podcast series was created to aid medical students studying for the Canadian Medical Council’s licensing exam. Each episode is created based on specific LMCC objectives and is divided into 2 parts. In part one we provide an overview of the topic with the help of experts in the field, followed by Part 2 where we review LMCC styled questions to help consolidate knowledge. In this episode, we welcome our expert advisor, Dr. Alice Cheng, Endocrinologist and Associate Professor at the University of Toronto to speak on LMCC Objective 37-2* Diabetes Mellitus. This episode was written by Susan Wang & Dr. Alice Cheng, edited by Esther Kang, Meryem Talbo and Katherine Lan. Please see our website www.mjmmed.com for more information, including a link to show notes.